Prevention of functional and cognitive impairment through a multicomponent exercise program during and after hospitalization of older adults (PREDISC): Study protocol for a multicenter randomized clinical trial - Nicolás Martínez-Velilla; Rosário Santos Silva; Patricia Alvarez Rodriguez; Jan Missé Xandri; Ana Pais; Encarna Ulloa Rodríguez; Gabor Abellan van Kan; Eva Peyrusque; Maite Izco-Cubero; Marisa Fernández González de la Riva; Regina Belo; Fabiola Zambom-Ferraresi; et al. (PLoS ONE, 2025)
Hospitalisation in older adults is frequently associated with a significant risk of functional and cognitive decline. This study aims to evaluate the effectiveness of a multicomponent exercise program designed to prevent such declines in acutely hospitalised older adults. The intervention will be implemented across three European hospitals with the goal of enhancing the quality of life and functional independence of this vulnerable population. This study will be conducted as a multicentre, randomised controlled trial with two arms: one group will receive a multicomponent exercise program, while the control group will receive standard care. The intervention will consist of individualised sessions focusing on resistance training, balance, and aerobic exercises over four days during hospitalisation. The primary outcome will focus on functional capacity, which will be assessed using the Short Physical Performance Battery. The primary outcome will be measured at baseline, discharge, and 30- and 90-days post-discharge. In addition to this primary outcome, secondary outcomes will include the Barthel Index, cognitive function assessed through the Mini-Mental State Examination, quality of life measured by the EuroQol-5D-3L, and psychological well-being evaluated using the Geriatric Depression Scale (GDS). Additional metrics will include length of hospital stay and readmission rates within 30- and 90-days post-discharge. Trial registration: ClinicalTrials.gov NCT06634147.